Predicting Psychological Wellbeing of Iranian Students Based on Attachment Styles and Internet Addiction in the Post-Corona Era - Qanadan, Farzane; Jafarzadeh, Mohammad Rahim (Journal of English Education Program, 2025)
The purpose of this research was to predict Iranian students' psychological well-being based on attachment styles and Internet addiction. The research design was descriptive and correlational. The current research population included 22131 fourth and fifth-grade students of Dezful City in the academic year"“2022-2023. The statistical sample was based on the cluster sampling table of Karjesi and Morgan (1970), resulting in 384 participants. They were administered the Riff psychological well-being questionnaire (short form), the Collins and Reed Adult Attachment Style Questionnaire (RAAS), and the Addiction to Internet Young test. The results showed that there is a direct and significant relationship between psychological well-being and secure attachment, and there is a direct and significant relationship with the variables of avoidant attachment and anxious attachment. Also, the results of the regression test showed that secure attachment, avoidant attachment, and anxious attachment significantly predicted psychological well-being. There is an indirect and significant relationship between Internet addiction and psychological wellbeing. Internet addiction significantly predicts the psychological well-being variable.